Investigation of flexural behaviour of polymer composite golf shaft. (2017) - Vijaya Ramnath, B.; Jeykrishnan, J.; Elanchezhian, C.; Kumar, Ashok; Narayan, Arvind
Abstract: Composite materials have been experimentally tested and manufactured for various sectors such as marine, industrial applications, aerospace, and sports. More notably recent years in sports field, composite materials have been effectively replaced for steel shafts which increase the comfort and accuracy of the player and moreover they have better mechanical properties according to the tests that have been performed and comparisons prove that composites are ideal replacements to steel shafts. In this work, polypropylene was used as used polymer matrix (PM) due to its unique strength and hardness. The flexural property of the polymer composite golf shaft was performed. These results will be useful in designing and fabricating polypropylene sheet rolled golf shafts.